F-108 The role of a dual pre- and post- entry innate and adaptive immune mechanism in protection against HIV-1 infection. (January 2016) - Wang, Yufei; Whittal, Trevor; Neil, Stuart; Britton, Gary; Rahman, Durdana; Mistry, Mukesh; Rerks-Ngarm, Supachai; Pitisuttithum, Punnee; Kaewkungwal, Jaranit; Nitayaphan, Sorachai; Michael, Nelson; Robb, Merlin; et al.
Abstract : The aim of this study was to examine the paradigm that a dual innate pre- and post-entry inhibition of HIV-1 may have been involved in the protective mechanism of the systemic Thai RV144, as observed in the London mucosal HIV-1 vaccine trial. In the Thai trial plasma MIP-1β was significantly upregulated within 2 weeks after the last immunization, followed by a decrease in CCR5 coreceptors of HIV-1, which inhibits entry of the virus into CD4+ T cells. APOBEC3G (A3G) and Tetherin mRNA in PBMC and A3G protein in CD4 CD45RO+ memory T cells were also upregulated. It is likely that these molecules were elicited by cellular stress of the RV144 vaccine, demonstrated by having induced HSP70, whilst the mucosal vaccine consists of an HIV-HSP70 conjugate. In both trials the mechanism involved pre-entry inhibition of transmission of the virus by the decreased availability of CCR5. Replication of any virus which gained entry into CD4+ T cells will have been inhibited by an increase in intracellular HIV-1 restriction factors. Importantly, the 3 CC chemokines showed significant direct correlation with the A3G restriction factor. In the Thai trial there was also a significant direct correlation between the vaccine induced innate CCR5 and the adaptive CD4+ T cell proliferative responses to HSP70. Furthermore, the dual innate immune mechanism was also found in alloimmunized women and in long-term non-progressors, suggesting that it may constitute a general protective mechanism against HIV-1 infection. This innate mechanism of pre-and post-entry inhibition of HIV-1 may contribute to the critical eclipse period and to subsequent adaptive immunity, which maintains H!V-1 inhibition.